2016
DOI: 10.21276/aimdr.2016.2.4.42
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study and Clinical Correlations of Mandibular Foramen in Dry Adult Human Mandibles of North Indian Origin

Abstract: Background:The mandibular foramen is located on the medial surface of ramus of mandible. It transmits inferior alveolar nerve. Inferior alveolar nerve block is a common procedure done by dental practitioners while doing various surgeries on mandible. The aim of this study is to determine the position of mandibular foramen in respect to various landmarks present on mandible. Methods: 30 adult human dry mandibles of north Indian origin were studied. The position of mandibular foramen from various landmarks was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Most of studies carried out on Egyptian population focused on anatomical variations of mandibular canal and mental foramen, thus to compensate for this shortage in previous studies we aimed to assess position of mandibular foramen using CBCT in Egyptian population. (13)(14)(15) This study evaluated the position of mandibular foramen in Egyptian population using CBCT. It is the most recent imaging technique in the maxillofacial imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Most of studies carried out on Egyptian population focused on anatomical variations of mandibular canal and mental foramen, thus to compensate for this shortage in previous studies we aimed to assess position of mandibular foramen using CBCT in Egyptian population. (13)(14)(15) This study evaluated the position of mandibular foramen in Egyptian population using CBCT. It is the most recent imaging technique in the maxillofacial imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Israr et al studied the position of the mandibular foramen in North Indian population. 8 In their study they found that the mandibular foramen was situated at a mean distance of 16.06±1.99 mm from the anterior border and 12.02±1.99 mm from the posterior border respectively. 93 edentulous mandibles of Indian origin were studied by Thangavelu et al in 2011 according to them the mandibular foramen was located at a mean distance of 18.9±2.14 mm on right side and 18.88±2.34 mm on the left side from the anterior border of ramus of the mandible.…”
Section: Discussionmentioning
confidence: 93%
“…Other authors, such as Oguz & Bozkir (2002) [ 15 ], Shenoy et al (2012) [ 17 ], Hoque et al (2013) [ 20 ], Gopalakrishna et al (2016) [ 21 ], Sultana et al (2016) [ 22 ], Khan & Ansari (2016) [ 23 ], Shalini et al (2016) [ 24 ], Lalitha et al (2016) [ 25 ], Rajkumari et al (2017) [ 26 ], and Sultana & Sreekanth (2019) [ 27 ], analyzed the topography of the MF only on dry edentulous mandibles, and their findings were different from those we are presenting in this study.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…As shown in a recent literature review [ 3 ], Khan & Ansari (2016) [ 23 ] have mentioned that the absence of specific bone landmarks, alongside variations in height and width of the mandibular ramus are causes of failure of the inferior alveolar nerve anesthesia.…”
Section: ⧉ Discussionmentioning
confidence: 99%